Phonotactic Constraints and Word Demarcation in Romance - João Veloso (2010)
In many languages, some phonological segments orstructures are allowed at word boundaries only. Theimportance of this fact is manifold: it shows that phonologyis not "blind" to the word as a linguistic unit; it can explainsome aspects of speech processing (how speech continuaare split into words); it may help to build software aimed atidentifying word boundaries within larger continua. ForEuropean Portuguese and for other Romance languagespossibly, it is proposed that a "Prosodic Tolerance of theWord Right Boundary" should play an important role as aphonotactic cue for word-endings: these languages areknown to be very restrictive as far as the segmental codafillingis concerned. However, these restrictions aresomehow cancelled at word-endings, which admitphonotactic combinations that are not allowed elsewhere. Aformalization of this phenomenon, inspired by the logicalformalisms of Declarative Phonology, is also proposed here.